POTENSI MICROLEARNING SEBAGAI STRATEGI PEMBELAJARAN BIOLOGI DI ERA DIGITAL - Kadek Yuniari Suryatini; Kadek Citra Wydia Putri; Maria Gresiana (SEMBIO: Prosiding Seminar Nasional Biologi dan Pendidikan Biologi, 2026)
The transformation of education in the digital era has brought about fundamental changes in learning. One approach that has developed in the digital era is microlearning. This article aims to examine the potential of microlearning as a strategy in biology learning in the digital era. This study uses a qualitative approach with descriptive methods. Research data were obtained through library research, involving the review of journal articles, books, and relevant research reports. Based on the results of the study, it shows that: (a) microlearning has great potential as a biology learning strategy in the digital era because it can provide learning that is more flexible, effective, and in accordance with the characteristics of today's students; (b) microlearning as a biology learning strategy supports the development of 21st-century skills such as digital literacy, critical thinking skills, and independent learning; and (c) The implementation of microlearning still faces several challenges, such as limited technological infrastructure, educators' readiness in designing digital content, and the potential for reduced material depth if content preparation is not carried out systematically.